Pengaruh Work-Life Balance dan Motivasi Kerja terhadap Kinerja Karyawan di PT Sumber Bintang Rejeki Semarang - Hia, Maifan Mariani; Hendrajaya, Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article analyzes the influence of Work-Life Balance and Work Motivation on Employee Performance in the manufacturing industry. Work-Life Balance is measured based on perceptions of time management, workload, and flexibility, while Work Motivation is seen from intrinsic factors (rewards, recognition) and extrinsic factors (incentives, career opportunities). The study used a quantitative approach with a survey of 100 respondents selected through purposive sampling. Multiple linear regression analysis showed that both variables had a positive and significant effect on employee performance, with a coefficient of ? = 0.312 for Work-Life Balance and ? = 0.428 for Work Motivation (p < 0.05). This study has limitations in sample size and sampling methods, which affect the generalizability of the results. Therefore, further studies are recommended using larger and random samples. These findings recommend companies to adopt flexible work policies, support work-life balance, and increase motivation through rewards and career development in order to increase employee productivity and retention sustaina